STRATEGI PEMASARAN MAKANAN OLAHAN PISANG SALE MELALUI MEDIA SOSIAL FACEBOOK (STUDI KASUS PADA USAHA TIRAM JAYA KABUPATEN ENREKANG) - Ummi Syafaat; Muh. Tamrin; Rahman Yakub; Andi Riska Andreani Syafaruddin (Bajang Institute, 2025)
The development of digital technology has driven a major transformation in marketing strategies, especially for micro, small, and medium enterprises (MSMEs) that utilize social media as a promotional tool. Facebook has become one of the most potential platforms due to its large number of users in Indonesia and its ability to reach consumers widely and interactively. This study aims to analyze the marketing strategies of processed Pisang Sale products implemented by Tiram Jaya Enterprise in Enrekang Regency through Facebook and to identify the challenges faced in improving the effectiveness of digital promotion. This research employed a quantitative descriptive approach with a population of 1,050 active followers of the Tiram Jaya Facebook account, and the sample was determined using the Slovin formula, resulting in 91 respondents. Data were collected through observation of promotional activities, documentation of digital content, and online questionnaires. The collected data were processed using the SPSS application through a series of statistical tests, including validity, reliability, normality, and heteroscedasticity tests, as well as simple linear regression analysis with t-test and F-test. The results show that the marketing strategy based on the marketing mix (7P) has a positive and significant effect on the effectiveness of Pisang Sale product promotion through Facebook, with a t-value of 9.114 and a significance level of 0.000. These findings confirm that optimizing the elements of product, price, place, promotion, people, process, and physical evidence can enhance consumer appeal, expand market reach, and strengthen the position of MSMEs in digital competition.